Quantitative and integrative analysis of paracrine hepatocyte activation by nonparenchymal cells upon lipopolysaccharide induction. (17th February 2017) - Beuke, Katharina; Schildberg, Frank A.; Pinna, Federico; Albrecht, Ute; Liebe, Roman; Bissinger, Michaela; Schirmacher, Peter; Dooley, Steven; Bode, Johannes G.; Knolle, Percy A.; Kummer, Ursula; Breuhahn, Kai; et al.
Abstract : Gut‐derived bacterial lipopolysaccharides (LPS) stimulate the secretion of tumour necrosis factor (TNF) from liver macrophages (MCs), liver sinusoidal endothelial cells (LSECs) and hepatic stellate cells (HSCs), which control the acute phase response in hepatocytes through activation of the NF‐κB pathway. The individual and cooperative impact of nonparenchymal cells on this clinically relevant response has not been analysed in detail due to technical limitations. To gain an integrative view on this complex inter‐ and intracellular communication, we combined a multiscale mathematical model with quantitative, time‐resolved experimental data of different primary murine liver cell types. We established a computational model for TNF‐induced NF‐κB signalling in hepatocytes, accurately describing dose‐responsiveness for physiologically relevant cytokine concentrations. TNF secretion profiles were quantitatively measured for all nonparenchymal cell types upon LPS stimulation. This novel approach allowed the analysis of individual and collective paracrine TNF‐mediated NF‐κB induction in hepatocytes, revealing strongest effects of MCs and LSECs on hepatocellular NF‐κB signalling. Simulations suggest that both cell types act together to maximize the NF‐κB pathway response induced by low LPS concentrations (0.1 and 1 ng/mL). Higher LPS concentrations (≥ 5 ng/mL) induced sufficient TNF levels from MCs or LSECs to induce a strong and nonadjustable pathway response. Importantly, these simulations also revealed that the initial cytokine secretion (1–2 h after stimulation) rather than final TNF level (10 h after stimulation) defines the hepatocellular NF‐κB response. This raises the question whether the current experimental standard of single high‐dose cytokine administration is suitable to mimic in vivo cytokine exposure. Database: The computational models described in this manuscript are available in the JWS database via the following link:https://jjj.bio.vu.nl/database/beuke Abstract : Inflammatory immune response in the liver involves the activation of the NF‐κB pathway in hepatocytes through cytokines like TNF that are produced by different types of cells in the liver after exposure to bacterial cell wall components. We integrate experimental data and computational models of the different cell types to gain quantitative understanding of the cell–cell interaction in the liver.